Searching for More Effective Food Baits for Tephritid Fruit Flies (Diptera: Tephritidae): Performance of Newly Developed Vial-Lures Relative to Torula Yeast Borax - Walther Enkerlin; Emilio Arevalo; Jose Eduardo Caballero; Thomas Fezza; Esteban Garavelli; Diana Beatriz Martinez; Pedro Alexander Rodriguez; Todd Shelly; Milthon Edgardo Thomas; Antonio Villaseñor; Salvador Flores (Insects)
Food-baited traps are an important part of early detection programs for invasive tephritid fruit fly species, as they are attractive to both sexes of all targeted species. Torula yeast borax (TYB) mixture is a standard food bait, but its longevity is limited (1–2 weeks). Synthetic food-based lures have been developed, including ammonium acetate, putrescine, and trimethylamine. However, the different formulations of these synthetic lures vary greatly in their attractiveness and longevity. Here, we present the results of field trapping in several Central and South American countries as well as Hawaii that compared captures of Ceratitis capitata, Anastrepha spp., and Bactrocera dorsalis in traps baited with torula yeast borax, which was replaced weekly, versus traps baited with newly developed vial-lures, which contained the same three components noted above and were not replaced over 6–10 weeks of trapping. In all countries, captures of C. capitata in vial-lure-baited traps were equal to or greater than captures in TYB-baited traps. However, the vial-lures attracted fewer B. dorsalis than TYB, and data were inconsistent for Anastrepha spp. The implications of these results for large-scale detection programs are discussed.